2015
DOI: 10.18097/pbmc20156101115
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of carbonate/bicarbonate ions in the superoxide-generating reaction of adrenaline autoxidation

Abstract: An important role of carbonate/bicarbonate ions has been recognized in the superoxide generating reaction of adrenaline autooxidation in an alkaline buffer (a model of quinoid adrenaline oxidation in the body). It is suggested that these ions are directly involved not only in formation of superoxide anion radical (О2 -·) but also other radicals derived from the carbonate/bicarbonate buffer. Using various buffers it was shown that the rate of accumulation of adrenochrome, the end product of adrenaline oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…The reaction of adrenaline autooxidation in the alkaline carbonate buffer was used for the determination of the SOD enzymatic activity, as a good model of the quinoid oxidation of adrenaline [29,30]. Scavenging superoxide anion-radical enzyme SOD inhibits the accumulation of adrenochrome.…”
Section: Sod-protective Activity and Pro-/antioxidant Activitymentioning
confidence: 99%
“…The reaction of adrenaline autooxidation in the alkaline carbonate buffer was used for the determination of the SOD enzymatic activity, as a good model of the quinoid oxidation of adrenaline [29,30]. Scavenging superoxide anion-radical enzyme SOD inhibits the accumulation of adrenochrome.…”
Section: Sod-protective Activity and Pro-/antioxidant Activitymentioning
confidence: 99%
“…The activity of SOD, which inhibited the formation of superoxide anion radical, was estimated by the literature method [24] and showed that the catalytic activity of SOD increased in the presence of both II and its complexes with I (Fig. 3).…”
Section: Lpo Processes In Blood Plasma Under Oxidative Stress In Vitrmentioning
confidence: 99%
“…•− (Scheme 1) [14][15][16][17][18][19][20]. Most of the information was obtained for significant conversion depths and refers to the hypothetical gross process of adrenaline → adrenochrome transformation [12,13,[15][16][17][18].…”
Section: Introduction 1the Base Mechanismsmentioning
confidence: 99%
“…•− (Scheme 1) [14][15][16][17][18][19][20]. Most of the information was obtained for significant conversion depths and refers to the hypothetical gross process of adrenaline → adrenochrome transformation [12,13,[15][16][17][18]. The detailed mechanism of the quinoid process is still actively discussed in the literature, and the role of magnetic fields is considered only from the standpoint of their possible effect on oxidative stress [1,4,7,14,[18][19][20][21].…”
Section: Introduction 1the Base Mechanismsmentioning
confidence: 99%